Characterization of T‐cell receptor transgenic mice recognizing immunodominant HLA‐DQ2.5‐restricted gluten epitopes. Issue 4 (28th December 2020) - Lindstad, Christian B.; Qiao, Shuo‐Wang; Johannesen, Marie K.; Fugger, Lars; Sollid, Ludvig M.; du Pré, M. Fleur
Abstract : We created a TCR transgenic mouse with CD4 + T cells recognizing the immunodominant DQ2.5‐glia‐ω2 gluten epitope. We show that these cells respond to deamidated gluten feed in vivo and compare them to previously published α2‐ and γ1‐specific mice. These mice may help enlighten key aspects of celiac disease pathogenesis.